The disintegration of the ruble zone: Driving forces and proposals for policy change - Lucjan T. Orlowski (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper examines the irreversible process of the ruble zone disintegration. Theoretical fundamentals of a common currency area, with modifications incorporating a mechanism of transition from central planning, are discussed. The key reason for the ruble zone break-up is the discontinuation of indirect transfers that were provided mainly by Russia via underpricing energy exports to other republics. Being cut-off from such transfers and unable to finance rising trade deficits with Russia, the independent stales wish to disconnect their economies from the ruble /.one. Among other economic arguments for leaving the ruble zone presented by the former Soviet republics are: a desire to insulate their economies from the ruble zone inflation, and a willingness to collect seigniorage revenues from printing their own currencies. The paper critically evaluates these and several other arguments. The abrupt break-up of the ruble zone causes interruptions in supplies of essential materials and consumer goods, and an income downfall among the republics. The foundation for a new inter-state payments mechanism is proposed in order to cushion these negative effects. A system of independently traded currencies with flexible exchange rates is viewed as a reasonable, yet distant solution.
Keywords: 330